On Irish absenteeism - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1851)
There are few questions in political economy on which a greater diversity of opinion has prevailed, than the one which I have selected as the subject of my paper this evening. Thus, some allege "that absenteeism is not prejudicial to the prosperity of a country; that Ireland, for instance, would suffer no detriment if all her proprietors should reside in foreign lands, and would derive no advantage from their return home to pass their lives, and spend their incomes in their own country." Whilst others contend "that the poverty of Ireland, the absence of capital and enterprize, her dilapidated resources, her unexplored treasures and unworked mines, her barren wastes, and, above all, her unemployed population, must be referred to the enormous sums of money withdrawn from the country in the shape of absentee rents;" in short, that absenteeism is "the monster evil of Ireland, from which almost all the evils that afflict the country either directly or indirectly arise." And between these extremes there are many intervening shades of opinion which it is unnecessary to notice.
Read January 23rd 1850
Keywords: Absentee landlords; Poverty; 314.15